2019
DOI: 10.3390/nano9010097
|View full text |Cite
|
Sign up to set email alerts
|

Magnetic-Plasmonic Heterodimer Nanoparticles: Designing Contemporarily Features for Emerging Biomedical Diagnosis and Treatments

Abstract: Magnetic-plasmonic heterodimer nanostructures synergistically present excellent magnetic and plasmonic characteristics in a unique platform as a multipurpose medium for recently invented biomedical applications, such as magnetic hyperthermia, photothermal therapy, drug delivery, bioimaging, and biosensing. In this review, we briefly outline the less-known aspects of heterodimers, including electronic composition, interfacial morphology, critical properties, and present concrete examples of recent progress in s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
18
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 20 publications
(18 citation statements)
references
References 251 publications
(380 reference statements)
0
18
0
Order By: Relevance
“…Magnetic-plasmonic heterodimers can be obtained by chemical synthesis (e.g., polyol method for Ag-FeCo hybrid NPs) [47], and can be composed of metallic-metallic or metallic-nonmetallic materials, such as Fe-Au heterodimers or Fe 3 O 4 -Au heterodimers, respectively. Due to the higher stability in biological media and the predominant hydrophilicity, metallic-nonmetallic hybrid MNPs are particularly interesting as host nanoparticles, and due to the potential applications, they urge as highly promising nanotheranostic agents [48].…”
Section: Hybrid Mnp Synthesismentioning
confidence: 99%
“…Magnetic-plasmonic heterodimers can be obtained by chemical synthesis (e.g., polyol method for Ag-FeCo hybrid NPs) [47], and can be composed of metallic-metallic or metallic-nonmetallic materials, such as Fe-Au heterodimers or Fe 3 O 4 -Au heterodimers, respectively. Due to the higher stability in biological media and the predominant hydrophilicity, metallic-nonmetallic hybrid MNPs are particularly interesting as host nanoparticles, and due to the potential applications, they urge as highly promising nanotheranostic agents [48].…”
Section: Hybrid Mnp Synthesismentioning
confidence: 99%
“…The most desired morphologies of the iron–gold NPs include core–shell, dumbbell-shaped, Janus-shaped, flower-shaped, star-shaped, octahedral-shaped, and rod-shaped, as depicted in Figure 2 . The synthesis of these morphologies, shape, and final performance depends on their junctional mode and interfacial morphology of the heterodimer structures [ 74 ].…”
Section: Iron–gold Bifunctional Nanoparticlesmentioning
confidence: 99%
“…Studies on the dumbbell heterodimers have demonstrated that the symmetry and free surface areas of dumbbell heterodimers are greater than those of randomly decorated ones, making them desirable for use in photo- and bio-catalysis applications [ 87 ]. The synthesis of the iron–gold heterodimers by the seed-mediated technique of non-spherical magnetic particles can affect their plasmonic properties during the interfacial morphology [ 74 ].…”
Section: Iron–gold Bifunctional Nanoparticlesmentioning
confidence: 99%
“…Thanks to their particular structure effects, plasmonic heteromers, possessing LSPR and other properties together via solid–solid nanointerface, have been applied in numerous fields, including photocatalysis, [ 90 ] electrocatalysis, [ 52a,91 ] optical sensing, [ 92,93 ] biomedical imaging, and cancer therapy. [ 75b,94,95 ]…”
Section: Properties and Applications Of Plasmonic Heteromeric Superstmentioning
confidence: 99%